Factor Structure, Convergent Validity, and Discriminant Validity of the NIH Toolbox Cognitive Health Battery (NIHTB-CHB) in Adults. (24th June 2014) - Mungas, Dan; Heaton, Robert; Tulsky, David; Zelazo, Philip David; Slotkin, Jerry; Blitz, David; Lai, Jin-Shei; Gershon, Richard
Abstract: The objective of this study is to evaluate the construct validity of the NIH Neurobehavioral Toolbox Cognitive Health Battery (NIHTB-CHB) in adults. Confirmatory factor analysis was used to evaluate the dimensional structure underlying the NIHTB-CHB and Gold Standard tests chosen to serve as concurrent validity criteria for the NIHTB-CHB. These results were used to evaluate the convergent and discriminant validity of the NIHTB-CHB in adults ranging from 20 to 85 years of age. Five dimensions were found to explain the correlations among NIHTB-CHB and Gold Standard tests: Vocabulary, Reading, Episodic Memory, Working Memory and Executive Function/Processing Speed. NIHTB-CHB measures and their Gold Standard analogues defined factors in a pattern that broadly supported the convergent and discriminant validity of the NIHTB-CHB tests. This 5-factor structure was found to be invariant across 20–60 year old ( N =159) and 65–85 year old ( N =109) age groups that were included in the current validity study. Second order Crystallized Abilities (Vocabulary and Reading) and Fluid Abilities (Episodic Memory, Working Memory, Executive/Speed) factors parsimoniously explained correlations among the five first order factors. These results suggest that the NIHTB-CHB will provide both fine-grained and broad characterization of cognition across the adult age span. ( JINS, 2014, 20, 1–9)